EMISSION OF MONOTERPENES AND ISOPRENE FROM A MEDITERRANEAN OAK SPECIES QUERCUS ILEX L. MEASURED WITHIN THE BEMA (BIOGENIC EMISSIONS IN THE MEDITERRANEAN AREA) PROJECT EMISSIONS IN THE M E D I T E - Kesselmeier, J; Fer, L S C H; Ciccioli, P; Brancaleoni, E; Cecinato, A; Frattoni, M; Foster, I P; Jacob, V; Denis, J; Fugit, J L; Dutaur, L; Torres, L; et al. (Atmospheric Environment, 1996)
We report on some results of our studies of monoterpene and isoprene emissions and the physiological activities of an oak species (Quercus ilex L.) under the Mediterranean climatic conditions found at Castel Porziano (Rome) in June 1993. The oak species Quercus ilex L. was found to emit mainly monoterpenes in high amounts. Isoprene emissions were negligible. Diel cycles of monoterpene emissions showed correlation with light and the diel behaviour of photosynthetic CO2 assimilation, transpiration and stomatal corductance. Temperature dependence seemed to be of minor importance.
Keywords: Biogenic emission; isoprene; light; Monoterpenes; non-methane hydrocarbons; oak; Plant physiology; VOC

Evidence of the photosynthetic origin of monoterpenes emitted by Quercus ilex L leaves by C-13 labeling - Loreto, F; Ciccioli, P; Cecinato, A; Brancaleoni, E; Frattoni, M; Fabozzi, C; Tricoli, D (PLANT PHYSIOLOGY, 1996)
The carbon of the four main monoterpenes emitted by Quercus flex L. leaves was completely labeled with C-13 after a 20-min feeding with 99% (CO2)-C-13. This labeling time course is comparable with the labeling time course of isoprene, the terpenoid emitted by other Quercus species and synthesized in leaf chloroplasts. It is also comparable with that of phosphoglyceric acid. Our experiment therefore provides evidence that monoterpenes emitted by Q. ilex are formed from photosynthesis intermediates and may share the same synthetic pathway with isoprene. By analyzing the rate and the distribution of labeling in the different fragments, we looked for evidence of differential carbon labeling in the alpha-pinene emitted. However, the labeling pattern was quite uniform in the different fragments, suggesting that the carbon skeleton of the emitted monoterpenes comes from a unique carbon source.
APS
Keywords: alpha-pinene; C-13 labeling; Emissions; isoprene; Monoterpenes; Quercus flex L.; Quercus ilex